A Competency‐Based Perspective on Entrepreneurship Education: Conceptual and Empirical Insights. (13th June 2013) - Morris, Michael H.; Webb, Justin W.; Fu, Jun; Singhal, Sujata; Vozikis, George; Solomon, George; Winkel, Doan
<x xml:space="preserve">Abstract</x> Competencies necessary for entrepreneurial action are investigated. Building on structuration theory, competencies are approached as an outgrowth of the learning of scripts deriving from interactions between the individual and environment. Managerial and entrepreneurial competencies are distinguished, with the latter helping to define the domain of entrepreneurship education. Employing a Delphi methodology, evidence is provided of a core set of 13 entrepreneurial competencies. Measures are then developed with a pilot study involving students in an international education program. Based on pre‐ and post‐measures, findings demonstrate significant improvement on the competencies. Implications are drawn for the role of entrepreneurship education in competency development.